Analisis Program Pencegahan dan Faktor Risiko Penyalahgunaan Narkoba pada Remaja: Studi Mixed Method di Kabupaten Sidenreng Rappang - Pannyiwi, Rahmat; Ali, Akhwan (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Drug abuse is a serious problem that threatens the future of adolescents in Indonesia, including in Sidenreng Rappang Regency (Sidrap). Adolescents are vulnerable due to environmental, family, and social factors. The purpose of this study was to analyze drug prevention programs and the risk factors associated with drug abuse among adolescents in Sidrap. This study used a mixed-method sequential explanatory design, beginning with a quantitative survey of 200 high school/vocational school adolescents and continuing with in-depth interviews with religious leaders, teachers, National Narcotics Agency (BNN) officers, and adolescents. The quantitative analysis showed that the main risk factors significantly associated with drug abuse were peer influence (p<0.05), poor family communication (p<0.05), and insufficient knowledge about the dangers of drugs (p<0.05). Meanwhile, qualitative findings revealed that existing prevention programs, such as school counseling and BNN campaigns, have not been optimal due to limited resources and low family involvement. The study's conclusions emphasize that drug prevention efforts must be implemented holistically through synergy between the government, schools, religious leaders, and families.